Meta‐analysis of oncological outcomes after local excision of pT1–2 rectal cancer requiring adjuvant (chemo)radiotherapy or completion surgery. Issue 9 (15th June 2016) - Borstlap, W. A. A.; Coeymans, T. J.; Tanis, P. J.; Marijnen, C. A. M.; Cunningham, C.; Bemelman, W. A.; Tuynman, J. B.
Abstract: Background: Completion total mesorectal excision (TME) is advised for high‐risk early (pT1/pT2) rectal cancer following transanal removal. The main objective of this meta‐analysis was to determine oncological outcomes of adjuvant (chemo)radiotherapy as a rectum‐preserving alternative to completion TME. Methods: A literature search using PubMed, Embase and the Cochrane Library was performed in February 2015. Studies had to include at least ten patients with pT1/pT2 adenocarcinomas that were removed transanally and followed by either adjuvant chemoradiotherapy or completion surgery. A weighted average of the logit proportions was determined for the pooled analyses of subgroups according to treatment modality and pT category. Results: In total, 14 studies comprising 405 patients treated with adjuvant (chemo)radiotherapy and seven studies comprising 130 patients treated with completion TME were included. Owing to heterogeneity it was not possible to compare the two strategies directly. However, the weighted average local recurrence rate for locally excised pT1/pT2 rectal cancer treated with adjuvant (chemo)radiotherapy was 14 (95 per cent c.i. 11 to 18) per cent, and 7 (4 to 14) per cent following completion TME. The weighted averages for distance recurrence were 9 (6 to 14) and 9 (5 to 16) per cent respectively. Weighted averages for local recurrence rate after adjuvant chemo(radiotherapy) and completion TME for pT1 were 10 (4 to 21) and 6 (3 to 15) per cent respectively. Corresponding averages for pT2 were 15 (11 to 21) and 10 (4 to 22) per cent respectively. Conclusion: A higher recurrence rate after transanal excision and adjuvant (chemo)radiotherapy must be balanced against the morbidity and mortality associated with mesorectal excision. A reasonable approach is close follow‐up and salvage mesorectal surgery as needed. Abstract : Salvage surgery may be superior